"النداءات الربانية في سورة المائدة - دراسة موضوعية- " - بية, هنية (University of Eloued جامعة الوادي, 2017)
حفل القرن الكريم بالكثير من الأساليب البلاغية الني اتخذها البلاغيون أساسا ومعلما من معالم البلاغة وركيزة من ركائزها في استقراء جماليات النص القرآني وتداعيات مدلولاته وتعابيره التي يقضيها من أسرار ببانه وأساليب طلبه. وأسلوب النداء هو فن في تلوين الخطاب وتنوع الأداء فهو خطاب من الله تعال إلى عباده على اختلاف أجناسهم وطوائفهم وذلك للامتثال لأوامره واجتناب نواهيه. وتقتصر الدراسة على نداءات الرحمان في سورة المائدة وقد وردت على ثلاث مستويات: نداءات للرسول - صلى الله عليه وسلم- خاصة ونداءات لأهل الإيمان عامة ونداءات لأهل الكتاب. وجاءت تحت عنون: "النداءات الربانية في سورة المائدة - دراسة موضوعية- " لقد اشتملت السورة على نداءات إلهية كثيرة منها ستة عشرة نداء للمؤمنين ونداءان من الله سبحانه وتعال لرسوله - صلى الله عليه وسلم- بصفة الرسالة الخاصة ولم يد مثلهما في غيرهما. ولأهل الكتاب خمسة نداءات، وتعد سور؛ المائدة أكثر السور الني تكرر فيها نداء المؤمنين" يا أيها الذين امنوا "حيث تكرر ستة عشرة مرة من أصل تسعة وثمانين نداء في القران الكريم وهذه النداءات تلخص المواثيق بين الله وعباده المؤمنين، كما ضمت أحكام شرعية ونصت على الوفاء بالعقود. The celebration of the Holy Century with many rhetorical methods adopted by the Balagians is a basis and a milestone in the rhetoric and a pillar of the extrapolation of the aesthetics of the Quranic text and the implications of its meanings and expressions, The style of the call is an art in the coloring of speech and diversity of performance is a speech of God come to worshipers of different races and sects and to comply with his orders and avoid his intentions. The study is limited to the calls of the Rahman in Surat Al-Maa'idah and has been answered on three levels: appeals to the Prophet - peace be upon him - especially appeals to the people of faith in general and appeals to the people of the book. It came under the heading of "the Lord's calls in Surat Al-Maeda - an objective study - Surah included many divine calls, including sixteen calls to believers and calls from God Almighty to His Messenger - peace be upon him - as a private message and did not like them in others. And the people of the book five calls, and Sur, the table is the most repeated wall of the call of believers, "O you who believe" where repeated sixteen times out of the ninety-nine appeal in the Koran and these calls summarize the charters between God and his worshipers, and included provisions of legitimacy and provided for Fulfillment of contracts.
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: النداءات الربانية - سورة المائدة – القرآن الكريم – الأساليب البلاغية; Al - Maida - The Holy Quran - The rhetorical methods